Play to read love to read unveiled: a personal literacy expedition - Abdullah, Nur Nabilah (Sejahtera Centre for Sustainability and Humanit, IIUM, 2023)
The author documents her literacy project aimed at assisting Orang Asli children, showcasing how these initiatives bridge academic knowledge with real-world community needs. The chapter, contributing to the book's narrative on 'Whole Society Transformation - Journey of Usrah in Action Implementation,' is organized around two distinct modules: "Usrah in Action 1" and "Usrah in Action 2." Central to these modules is the concept of "Communiversity," which fosters a collaborative partnership between the university and the community.